Construction of the osteochondral graft using a live hyaline cartilage graft and sintered microspheres scaffold - Song, Fengting (2016)
Articular hyaline cartilage in the knee joint is crucial for smooth movement and support of the bone conjunction. Cartilage lacks self-healing abilities once injured because of its avascular property. What’s more, cartilage damage could also lead to osteoarthritis, a degenerative joint disease which might cause pain and disability. Therefore surgical treatment is always required to replace the damaged cartilage. However, the average long term result of the treatments such as mosaicplasty, debridement, autologous chondrocyte implantation is not satisfactory. Tissue engineering approach is the art of using appropriate cells and biomaterials to restore articular cartilage function by developing cartilage graft for replacement. Osteochondral grafts have demonstrated significant potentials and gained more attentions in recent years. Osteochondral graft consists of cartilage layer and bone layer. Theoretically, bone-to-bone healing is much easier than cartilage healing, so that the osteochondral graft has better integration with host tissue. Our lab has developed a live hyaline cartilage graft (LhCG) and demonstrated its cartilage repair ability in animal models. Besides pure autologous chondrocytes, LhCG also includes the ECM which is based on a micro-cavity hydrogel and then secreted by themselves. In this project, an osteochondral graft including a cartilage layer (LhCG) and a bone layer is proposed to achieve better integration for further application. The bone layer is constructed using a sintered microspheres scaffold. To construct the scaffold, poly (lactide-co-glycolide) (PLGA) is first fabricated into microspheres followed by heat sintering to form a porous hard scaffold. Eventually the LhCG layer and sintered microspheres scaffold layer is combined together for the fabrication of an osteochondral graft.